Deep ultraviolet emission in hexagonal boron nitride grown by high-temperature molecular beam epitaxy. (17th March 2017) - Vuong, T Q P; Cassabois, G; Valvin, P; Rousseau, E; Summerfield, A; Mellor, C J; Cho, Y; Cheng, T S; Albar, J D; Eaves, L; Foxon, C T; Beton, P H; et al.
Abstract: We investigate the opto-electronic properties of hexagonal boron nitride grown by high temperature plasma-assisted molecular beam epitaxy. We combine atomic force microscopy, spectroscopic ellipsometry, and photoluminescence spectroscopy in the deep ultraviolet to compare the quality of hexagonal boron nitride grown either on sapphire or highly oriented pyrolytic graphite. For both substrates, the emission spectra peak at 235 nm, indicating the high optical quality of hexagonal boron nitride grown by molecular beam epitaxy. The epilayers on highly oriented pyrolytic graphite demonstrate superior performance in the deep ultraviolet (down to 210 nm) compared to those on sapphire. These results reveal the potential of molecular beam epitaxy for the growth of hexagonal boron nitride on graphene, and more generally, for fabricating van der Waals heterostructures and devices by means of a scalable technology.